Farmer soil health training report - Kaushal, Manoj; Atie, Willis (2025)
The Soil Health Training was conducted to strengthen farmers’ understanding of soil fertility management, soil conservation, and the use of affordable natural inputs. This activity forms part of ongoing initiatives promoting climate-smart agriculture and enhancing productivity among smallholder farmers in the region.